2022
DOI: 10.1039/d1tc05403a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the sign of circularly polarized emission in achiral polymer – chiral small molecule blends as a function of blend ratio

Abstract: Circularly polarized organic light-emitting diodes (CP-OLEDs) that demonstrate both state-of-the-art efficiency and strongly circularly polarized (CP) electroluminescence have proved a considerable technical challenge. Furthermore, multiple factors – from film thickness...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…They have a g EL of À0.65 and 0.3, respectively. 81,82 These results indicate that F8BT with chiral helical structure has great application potential in CP-OLED. [78][79][80]82 In 2020, Zou et al found that after the irradiation of left-handed or right-handed CPL light, the CPL signal can be measured from achiral luminescent polymer F6BT.…”
Section: Cpl Based On Chiral Induced Helical Polymersmentioning
confidence: 78%
See 1 more Smart Citation
“…They have a g EL of À0.65 and 0.3, respectively. 81,82 These results indicate that F8BT with chiral helical structure has great application potential in CP-OLED. [78][79][80]82 In 2020, Zou et al found that after the irradiation of left-handed or right-handed CPL light, the CPL signal can be measured from achiral luminescent polymer F6BT.…”
Section: Cpl Based On Chiral Induced Helical Polymersmentioning
confidence: 78%
“…They have a g EL of −0.65 and 0.3, respectively. 81,82 These results indicate that F8BT with chiral helical structure has great application potential in CP-OLED. 78–80,82…”
Section: Cpl Based On Chiral Induced Helical Polymersmentioning
confidence: 86%
“…10,13 Fuchter, Campbell and coworkers have demonstrated that annealed thin films of blends consisting of a conventional (achiral) electroluminescent polymer and a chiral small molecule additive, 1aza [6]helicene (hereafter, aza [6]H), can exhibit a considerable chiroptical response due to the induction of a chiral phase within the polymer. 9,[14][15][16][17][18] One of the challenges in developing highperformance CP-PLEDs is to identify chiral small molecule additives that (i) have appropriate energy levels to facilitate efficient charge injection and transport and (ii) induce the chiral phase.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Such devices still exhibit high V L (410 V) and poor luminance, with |g EL | that is sensitive to the position of the recombination zone. 9,[16][17][18]21,22 Considering the benefits of the EDA in non-CP PLEDs, we questioned whether a combination of three components (i.e., an achiral polymer, a chiral small-molecule additive and the EDA) may present an alternate approach to improve the performance of CP-PLEDs. The key challenge is to maximize the ternary synergetic effect for improved device efficiencies while maintaining the chiral polymer phase that gives rise to high |g EL |.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation